Algebraic Expressions
      Factoring algebraic expressions - methods, the greatest common factor
         Factoring by grouping
         Perfect square trinomials - the square of a binomial
         The difference of two squares
         Factoring quadratic trinomials
         The sum and difference of cubes
Factoring algebraic expressions
Factoring algebraic expression by finding (determining) the greatest common factor
Examples:   a)  3x - 6y = 3 (x - 2y),     b)  xy - y = y (x - y),     c)  a - a = a (1 - a),
d)  x3 -3x+ x = x (x2 - 3x +1),    e)  x(a + b) - (a + b) = (a + b) (x - 1),
f)   a(x - 3y) - x + 3 = a(x - 3y) - (x - 3y) = (x - 3y) (a - 1).
Grouping like terms, grouping and factorizing four terms
An addition sign, or plus sign, in front of the brackets leaves the sign of every term inside the brackets unchanged.
A minus sign in front of the bracket indicates that, when removing the bracket, the sign of all terms inside must be changed.
Examples:   a)  ax - bx - a + b = x(a - b) - (a - b) = (a - b) (x - 1),
b)  a - 1 - ab + b = (a - 1) - b (a - 1) = (a - 1) (1 - b),
c)  x2 + ax - bx - ab = x(x + a) - b (x + a) = (x + a) (x - b),
d)  5ab2 - 3a3 - 10b3 + 6a2b = 5b2(a - 2b) -3a2(a - 2b) = (a - 2b)(5b2 - 3a2).
Perfect square trinomials - the square of a binomial
Examples:   a)  1 - 4x + 4x2 = 1- 2 2x + (2x)2 = (1 - 2x)2  = (1 - 2x) (1 - 2x),
b)  a5 + 6a4b + 9a3b2 = a3 (a2  + 6ab  + 9b2 ) = a3(a + 3b)2 = a3(a + 3b)(a + 3b).
The difference of two squares
Examples:   a)  16x2 - 1 = (4x)2 - 12 = (4x -1) (4x +1),
b)  5y3 - 20x2y = 5y (y2 - 4x2) = 5y [y - (2x)2] = 5y(y - 2x)(y + 2x),
          c)   9x- (x + 2)2 = [3x - (x + 2)] [3x + (x + 2)] = (2x -2) (4x + 2) = 4(x -1) (2x +1).
Factoring quadratic trinomials
A quadratic trinomial  ax2 + bx + can be factorized as
ax2 + bx + c = a[x2 + (b/a)x + c/a] = a(x - x1)(x - x2) where x1 + x2 = b/a and  x1 x2 = c/a
That means, to factorize a quadratic trinomial we should find such a pair of numbers x1 and x2 whose sum equals b/a and whose product equals c/a.
Therefore, when the constant term c is negative, then the signs of x1 and x2 will be different but when c is positive, their signs will be the same.
Examples:   a)  x2 - 3x -10 = x2 + (-5 + 2)x + (-5)(+2) = x2 - 5x + 2x -10 =
                         = x (x - 5) + 2 (x - 5) = (x - 5) (x + 2),
b)  2x2 - 7x + 3 = 2 (x2 - 7/2x + 3/2) =  2(x2 - 1/2x - 3x + 3/2) =
                        = 2[x(x - 1/2) - 3 (x - 1/2)] = 2 (x - 1/2)(x - 3) = (2x - 1) (x - 3),
c)  3x2 - x - 2 = 3(x2 - 1/3x - 2/3) =  3(x2 + 2/3x - x - 2/3) =
                        = 3[x(x + 2/3) - (x + 2/3)] = 3(x + 2/3)(x - 1) = (3x + 2)(x - 1).
The sum and difference of cubes
Examples:   a)  x3 + 8 = x3 + 23 = (x + 2) (x2 - 2x + 22),
                        since  (x + 2)(x2 - 2x + 4) = x3 - 2x2 + 4x + 2x2 - 4x + 8 = x3 + 8,
b) 8a3 -125 = (2a)3 - 53 = (2a - 5) [(2a)2 + (2a)5 + 52] = (2a - 5)(4a2 + 10a + 25),
  since  (2a - 5)(4a2 + 10a + 25) = 8a3 + 20a2 + 50a - 20a2 - 50a -125 = 8a3 -125.
Intermediate algebra contents
Copyright 2004 - 2020, Nabla Ltd.  All rights reserved.